The pecan : a history of America's native nut - McWilliams, James E. (Austin : University of Texas Press, 2013)
"In The Pecan, acclaimed writer and historian James McWilliams explores the history of America's most important commercial nut. He describes how essential the pecan was for Native Americans--by some calculations, an average pecan harvest had the food value of nearly 150,000 bison. McWilliams explains that, because of its natural edibility, abundance, and ease of harvesting, the pecan was left in its natural state longer than any other commercial fruit or nut crop in America. Yet once the process of "improvement" began, it took less than a century for the pecan to be almost totally domesticated. Today, more than 300 million pounds of pecans are produced every year in the United States--and as much as half of that total might be exported to China, which has fallen in love with America's native nut. McWilliams also warns that, as ubiquitous as the pecan has become, it is vulnerable to a "perfect storm" of economic threats and ecological disasters that could wipe it out within a generation. This lively history suggests why the pecan deserves to be recognized as a true American heirloom."--Jacket.
Introduction : Cracking the nut -- The Native Americans' nut -- "Pekan Nuttrees" : Europeans encounter the pecan -- " ... the forest into an orchard" : passive cultivation on the Texas frontier -- Antoine's graft : the birth of the improved pecan, 1822-1900 -- "To make these little trees" : the culture of pecan improvement, 1900-1925 -- "Pecans for the world" : the pecan goes industrial, 1920-1945 -- "In almost any recipe ... pecans may be used" : American consumers embrace the pecan, 1940-1960 -- "China wants our nuts" : the pecan goes global -- Epilogue : The future of pecans.
Includes bibliographical references and index.
Keywords: Pecan; Pecan industry; Pecan; Pecan industry; Pekannuss; Pekannussanbau; Pecans; Nuts